PENGARUH REINVENTING POLICY, PELAYANAN FISKUS DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - RIONALDO SANJAYA; HARYO SUPARMUN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to analyze the effect of reinventing policy, tax officer services, and tax penalties on tax compliance in KPP Pratama Jakarta Cengkareng. Primary data are collected through questionnaires dissemination to tax payers at KPP Pratama Jakarta Cengkareng. The population is all registered taxpayer in KPP Pratama Jakarta Cengkareng. The number of sample are 94 respondents. The purposive sampling method is used to select the sample. The data analysis are validity test, reliability test, classical assumption test, the coefficient determination analysis (adj.R2), simultaneous regression test (F test), and partial regression test (t test). Based on the data analysis, the results show the reinventing policy does not have significant effect on tax compliance, while tax officer services and tax penalties have significant effect on tax compliance.